PERAN MEDIA ARUS UTAMA DALAM MEMUBLIKASIKAN PRODUK MAKANAN HALAL - Suyono Suyono (MEDIAKOM : Jurnal Ilmu Komunikasi, 2020)
This study uses a qualitative descriptive approach, by observing / observing related mainstream Media roles in publishing Halal food products. Refer to the Law (UU) Number 33 year 2014 on the Halal Product Guarantee (JPH), which will be effective 17 October 2019, then food products, beverages, and other products that are circulating and traded in the region of Indonesia must be certified Halal. Halal products are products (food, beverages, etc.) that are processed and produced halal. The same is the case with materials and the process should also be halal. Halal Certificate In fact protects Muslim consumers against unkosher products and beverages, provides a sense of security and comfort to consume them, because there is no doubt that the product is indicative of the things that are haraam According to Islamic law. Although the validity period has lived a few more months, but the reverb enforcement of the law No. 33/2014, not yet loud heard in the community. Hence, the authors are interested in researching how much mainstream media roles (mainstream media, especially newspapers and television) are participating in publishing halal product guarantees, in the announcement. From the author's research, apparently mainstream media has not contributed much in the community to realize the production and also consume halal products. Although some food producers, drinks and beauty equipment, have been conducting socialization activities through advertising in the media, especially on television, by listing the halal logo from LPPOM-MUI, in the ad packaging that served.